Bioresorbable scaffold implantation in patients with indication for oral anticoagulation: A propensity matched analysis. (15th March 2017) - Boeder, Niklas F.; Johnson, Victoria; Dörr, Oliver; Wiebe, Jens; Elsässer, Albrecht; Möllmann, Helge; Hamm, Christian W.; Nef, Holger M.; Bauer, Timm
Abstract: Objectives: To examine ischemic and bleeding outcomes in patients on triple antithrombotic therapy (TAT) compared with dual antiplatelet therapy (DAPT) after the implantation of bioresorbable scaffolds (BRS). Background: The optimal antithrombotic regimen in patients undergoing percutaneous coronary intervention that have an indication for oral anticoagulation is unclear, in particular among those undergoing BRS implantation. Methods: Consecutive patients of a single-center, all-comers BRS registry were included. Patients were followed up after 30 days, 6 and 12 months, and thereafter yearly. Outcome parameters were target vessel failure (TVF), major adverse cardiac events (MACE) including target lesion revascularization (TLR), scaffold thrombosis (ST), death, myocardial infarction, and any bleeding as defined by BARC. Patients on TAT were matched to patients on DAPT. Results: A total of 607 patients were included. Fifty-five patients receiving TAT were matched with 165 patients treated with DAPT. Acute coronary syndrome was an indication for coronary angiography in 50.9% vs 50.4% groups ( p  = 0.97). Major adverse cardiac events occurred in 16.4% of TAT patients vs. 8.9% DAPT patients ( p  = 0.12), TLR in 5.5% vs. 1.9% ( p  = 0.17), ST in 3.6% vs. 1.9% ( p  = 0.46), and TVF in 3.6 vs. 1.9% ( p  = 0.46). Patients died in 7.3% in the TAT group vs. 5.1% in the DAPT group ( p  = 0.26). No severe bleeding was recorded in either of the groups. Conclusion: There was no difference in bleeding or ischemic events between the patients on TAT and those on DAPT after BRS implantation. The high rate of scaffold thrombosis in all of these patients, however, is not negligible.